Lymph Node Metastasis From Gastroesophageal Cancer Successfully Treated by Nivolumab: A Case Report of a Young Patient - Kashima, Shin; Tanabe, Hiroki; Tanino, Mishie; Kobayashi, Yu; Murakami, Yuki; Iwama, Takuya; Sasaki, Takahiro; Kunogi, Takehito; Takahashi, Keitaro; Ando, Katsuyoshi; Ueno, Nobuhiro; Moriichi, Kentaro; et al. (Frontiers in Oncology, 2019)
Background: Immuno-oncology is a novel target of cancer therapy. Nivolumab is a monoclonal anti-programed death-1 antibody recently used to treat patients with chemotherapy-resistant gastric and gastroesophageal cancer. Although the disease control rate is reported to be very high, few cases demonstrate a complete response. Case Presentation: A 25-year-old man diagnosed with gastroesophageal cancer was treated with chemotherapy followed by surgical resection. Pathological diagnosis was poorly differentiated adenocarcinoma with distant lymph node metastasis. Residual lymph node metastasis was treated with nivolumab monotherapy, resulting in complete disappearance. No recurrence has been observed for two years since discontinuation of nivolumab. This rare case was additionally subjected to pathological and genetic analysis, suggesting that a high tumor mutation burden (10.7 mutations/Mb) might be associated with sensitivity to nivolumab. Summary: We reported a case of advanced gastroesophageal junction cancer with distal lymph node metastasis that was successfully treated with chemotherapy, surgical resection, and nivolumab therapy. An aggressive search for biomarkers implying benefit effects of nivolumab should be performed.